A Study on Consumer Preferences and Satisfaction Towards Digital Lending - Rajasekar, S; Jagadeesan, P. (Journal of Neonatal Surgery, 2025)
Digital lending has revolutionized the way consumers access credit, offering a convenient, fast, and personalized alternative to traditional banking methods. As digital platforms increasingly become the preferred method for obtaining loans, understanding consumer preferences and satisfaction becomes essential. This study explores the factors that drive consumer choice in digital lending, including convenience, speed, transparency, cost effectiveness, and personalized offerings. It highlights how these features significantly enhance consumer satisfaction, making digital lending more appealing than traditional lending methods. Additionally, the study examines challenges such as data security, eligibility concerns, and the lack of physical interaction, which can impact consumer trust and satisfaction. Ultimately, the research underscores the growing role of digital lending in meeting modern consumer expectations and its potential for continued growth and innovation in the financial services sector..